Shifting Spaces in the Critical Regionalist Fiction of New England - Schulte, Marleen (Current Objectives of Postgraduate American Studies, 2012)
At the turn of the twenty-first century, a critical regionalist fiction is emerging. Like its architectural counterpart, this fiction fuses the local with the global by situating current issues in a particular place, simultaneously exerting an emancipatory action. Whether North Dakota, Newfoundland, or Maine, these are places off the literary map. This article explores how critical regionalist fiction is shifting the physical, imagined, and lived spaces of New England.